2017
DOI: 10.1108/ijlma-07-2016-0063
|View full text |Cite
|
Sign up to set email alerts
|

“Another nice mess you’ve gotten me into” employers’ liability for workplace banter

Abstract: Purpose Banter has been defined in the Oxford Dictionary as “the playful and friendly exchange of playful remarks” [www.merriam-webster.com/dictionary/banter]. This suggests that it is a form of dialogue or conversation that is welcome, non-threatening and appreciated by the recipient. However, this is often not the case, and the purpose of this paper is to consider the legal rules dealing with banter where it is threatening, unwanted or oppressive to the recipient. Where there is a discriminatory aspect to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Although the majority of respondents stated they would not ban banter, we found that only one third were confident that their organisations had appropriate policies and procedures in place. Furthermore, banter may be used within the workplace in ways that breach basic human rights [5]. Although our respondents provide very balanced views of banter, for example one stated "I feel that it has been part of life from the playground to work place, it is part of our culture and I have experienced this across the different countries that I have worked", it is important to have easily accessible support available for anyone that is a victim of unwanted behaviour.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Although the majority of respondents stated they would not ban banter, we found that only one third were confident that their organisations had appropriate policies and procedures in place. Furthermore, banter may be used within the workplace in ways that breach basic human rights [5]. Although our respondents provide very balanced views of banter, for example one stated "I feel that it has been part of life from the playground to work place, it is part of our culture and I have experienced this across the different countries that I have worked", it is important to have easily accessible support available for anyone that is a victim of unwanted behaviour.…”
Section: Discussionmentioning
confidence: 96%
“…At the level of legislation, it is also challenging to define acceptable conduct for banter. Within the UK, under article 8 of the 1998 Human Rights Act, workers have the right to a private and family life, however banter may breach these basic human rights [5]. Additionally, article 14 state that workers have the right to freedom of religion, freedom of expression and freedom from discrimination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20. Conn v Council of City of Sunderland (2008) IRLR 324 see fuller discussion of this remedy in Middlemiss (2017). …”
Section: Notesmentioning
confidence: 99%
“…In recent decades, research literature has rather widely studied one of the subgroups of covert antisocial behaviour bullying and harassment (for example, only a few of them: Leymann, 1993;Zapf, 1999;Prummer & Hasmuller, 2015;Merilainen et al, 2015;Barasuol et al, 2017;Chandrasiri, 2017;Middlemiss, 2017;etc.). The analysis of the prevalence of this phenomenon in various social contexts often focuses on the school environment (Gill, Larsson, 2014;Evans et al, 2016;Kowalski, 2017) concluding that young people often face bullying and harassment, which also results in the abundance of research conducted in the educational system (Patton et al, 2017).…”
Section: Introductionmentioning
confidence: 99%